(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article analyzes dichotomous worldviews within antonymic frames from a cognitive linguistic perspective. Using frame semantics, corpus analysis, and associative testing, the study explores cases of semantic asymmetry in antonymic pairs. The findings reveal that antonyms are structured not symmetrically but around evaluative centrality. Central lexemes, often negatively marked, are cognitively more active and salient in discourse. Examples such as “ҳалол – ҳаром,” “ифлос – пок,” and “вайрон – обод” are used to model these conceptual oppositions. This approach has both theoretical and practical relevance for lexicology, cognitive linguistics, and educational discourse.